SISTEM INFORMASI KEPEGAWAIAN DI LPP RADIO REPUBLIK INDONESIA JAMBI - Ediansa, Oka; Akbar, Zulfikri; Kurniawansyah, Kevin (LPPM Universitas Muhammadiyah Jambi, 2023)
Management of personnel administration data in an organization or agency/institution plays an important role in the administrative process. In this case the current personnel information system has a weakness, namely it is only used to record employee attendance and only involves one user and only uses one computer. With this desktop-based staffing system, it can help the process of managing personnel data at LPP RI Jambi so that it becomes more effective and efficient. The design of a desktop-based personnel administration system can make it easier for admins to input data, reduce time, and minimize the possibility of errors in recording. As well as designing a personnel information system at LPP RI Jambi using a desktop-based modeling technique made with the Delphi 7 programming language and mysql database. In describing system analysis and design, namely in the form of DFD (Data Flow Diagram) and ERD (Entity Relationship Diagram). The output of this study is the design of the analysis system and the design of a staffing information system at LPP RI Jambi.